Development of an Inventory Dashboard Module for Enterprise Resource Planning (ERP) at PT. Mitra Kasih Perkasa - Jonathan Christiawan; Albertus Dwiyoga Widiantoro; T. Brenda Chandrawati (Soegijapranata Catholic University, 2026)
Businesses are growing more conscious of the value of information technology in today's digital age in order to maximize operations and decision-making. The fintech company PT. Mitra Kasih Perkasa frequently has challenges with data management and transactions since it needs an integrated ERP application. The goal of PT. Mitra Kasih Perkasa's inventory dashboard module development for the Enterprise Resource Planning (ERP) system is to increase the efficacy and efficiency of the business operations of the organization.This dashboard module is intended to integrate many business operations into a single platform and offer simple access and monitoring of inventory activity. Rapid Application Development (RAD), a development methodology that enables quick and flexible development, is employed. User input on the system's usability and functioning is gathered through testing with questionnaires that are provided to users.The test results show that this ERP dashboard's easy design, strong integration, and user-friendly functionality effectively satisfy user demands. Accordingly, this module may increase PT. Mitra Kasih Perkasa's operational efficiency and streamline all business operations.